Artificial Intelligence in Engineering Education - B. A. Levin; A. A. Piskunov; V. Yu. Poliakov; A. V. Savin (Высшее образование в России)
Due to the growing interest in artificial intelligence in recent years, teaching this discipline to students of applied technical specialties is becoming relevant. Despite the formation of this scientific direction for almost 70 years, there is still no clear understanding of the terminology of this science, its tasks at the present stage and its application in engineering education. Moreover, the artificial intelligence terminology often misleads students. The article examines the current situation with the development of ideas related artificial intelligence, the possibility of its using in engineering education. Based on the analysis of the real possibilities of artificial intelligence, the actual content of education in the discipline of “Artificial intelligence in transport construction” is determined. The article focuses on users of artificial intelligence, not developers. The authors consider the competencies of a specialist that can be formed during the study of the above indicated discipline, as well as new relevant competencies that are necessary for a specialist in connection with the wide dissemination of artificial intelligence in the conditions of his/her professional activity. The functional model of artificial intelligence used in teaching students how to interact with it is considered. The article gives the examples of tasks solved by students today with the help of artificial intelligence technology during trial training.